2018
DOI: 10.2147/ijn.s155228
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of zinc and copper content in tooth enamel without any pathological changes – an in vitro study

Abstract: ObjectivesThe objectives of the study were to evaluate the content of copper and zinc in individual layers of tooth enamel and to analyze the relationships between the study minerals in individual layers of tooth enamel.Patients and methodsFifteen human permanent teeth were cut off every 150 μm alongside the labial surface. Acid biopsy of each layer was performed. The zinc content was determined using the air–acetylene flame method. The copper content was determined using the electrothermal technique with argo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Zinc exchange from the posteruptive oral environment may well contribute to this surface enrichment (Humphrey et al 2008a) but it is notable in this study that worn enamel, despite having being exposed to saliva, is not Zn rich. Zinc at the enamel surface has also been tentatively linked to the intense involvement of Zn in the process of enamel mineralisation and maturation (Humphrey et al 2008a;Klimuszko et al, 2018;Müller et al, 2019).…”
Section: Zinc In Enamel and Dentinementioning
confidence: 99%
See 2 more Smart Citations
“…Zinc exchange from the posteruptive oral environment may well contribute to this surface enrichment (Humphrey et al 2008a) but it is notable in this study that worn enamel, despite having being exposed to saliva, is not Zn rich. Zinc at the enamel surface has also been tentatively linked to the intense involvement of Zn in the process of enamel mineralisation and maturation (Humphrey et al 2008a;Klimuszko et al, 2018;Müller et al, 2019).…”
Section: Zinc In Enamel and Dentinementioning
confidence: 99%
“…Zinc reaches highest levels in the ameloblast nucleus during enamel maturation and Zn a component of alkaline phosphatase, of carbonic anhydrase, of MMP-20 and KLK4 (Klimuszko et al, 2018). Zinc is also a potent inhibitor of serine proteases including KLK4 and so may act to modulate enamel protein degradation.…”
Section: Zinc In Enamel and Dentinementioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Other factor that may affect copper ions is that the copper ions contained in teeth created a protective layer in the form of copper (II) phosphate (Cu 3 (PO 4 ) 2 ) on the enamel surface, thus making the enamel more resistant to environmental changes, especially acidic environment. 9 The results of this study showed that copper ion release on peat water group was less than immersion in artificial saliva and tap water. This may be caused by adsorption reaction between hydroxyapatites and free copper ions in the solution.…”
Section: Discussionmentioning
confidence: 67%
“…Copper ions are also able to become cariostatic agents by inhibiting the development and metabolism of bacteria. 9 Aside from copper ions, other minerals that can be released when the teeth are exposed to acids are selenium ions (Se 4+ ). The presence of selenium ions in tooth can increase the susceptibility of teeth to caries.…”
Section: -mentioning
confidence: 99%